2019
DOI: 10.1128/iai.00695-19
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa ExsA Regulates a Metalloprotease, ImpA, That Inhibits Phagocytosis of Macrophages

Abstract: Pseudomonas aeruginosa is an opportunistic pathogenic bacterium whose type III secretion system (T3SS) plays a critical role in acute infections. Translocation of the T3SS effectors into host cells induces cytotoxicity. In addition, the T3SS promotes the intracellular growth of P. aeruginosa during host infections. The T3SS regulon genes are regulated by an AraC-type regulator, ExsA. In this study, we found that an extracellular metalloprotease encoded by impA (PA0572) is under the regulation of ExsA. An ExsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…We observe that knockdown of CD44 reduces the levels of internalization of C. burnetii without affecting bacterial adhesion to HeLa cells that could depend mainly on the α v β 3 integrins. Our results are consistent with a recent work which demonstrated that CD44 knockdown in macrophages produces lower levels of internalization of S. aureus without affecting its adhesion to the cell (Li et al., 2018) or inhibits phagocytosis of P. aeruginosa (Tian et al., 2019).…”
Section: Discussionsupporting
confidence: 93%
“…We observe that knockdown of CD44 reduces the levels of internalization of C. burnetii without affecting bacterial adhesion to HeLa cells that could depend mainly on the α v β 3 integrins. Our results are consistent with a recent work which demonstrated that CD44 knockdown in macrophages produces lower levels of internalization of S. aureus without affecting its adhesion to the cell (Li et al., 2018) or inhibits phagocytosis of P. aeruginosa (Tian et al., 2019).…”
Section: Discussionsupporting
confidence: 93%
“…PA0572 from Pseudomonas aeruginosa was identified as a protease by its ability to cleave glycoproteins involved in leukocyte homing, thus compromising immune function and leading to the enzyme being called IMPa (immunomodulating protease of Pseudomonas aeruginosa) (Bardoel et al, 2012). Through its ability to cleave CD44, IMPa also inhibits phagocytosis (Tian et al, 2019). This secreted effector, therefore, is a potentially important factor in the hostpathogen interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary analysis of scanning the genome for the conserved ExsA-binding motif ( 41 ) identified four putative type III effectors (DNA polymerase IV, TonB-dependent receptor, heme-binding protein, and response regulator transcription factor) (data not shown). However, it is important to note that ExsA has also been reported to regulate the expression of non-T3SS genes, including the metalloprotease impA and other secretory proteins in P. aeruginosa ( 42 ). Thus, it remains to be determined biochemically if there are additional T3SS effector proteins in P. lundensis , but there are some potential targets.…”
Section: Discussionmentioning
confidence: 99%